Developing Optical Imaging Tools to Investigate Metabolic and Structural Biomarkers in Rodent Injury Models - (:unkn) unknown (My University, 2021)
Optical fluorescence imaging is one of the vastly growing fields of imaging used in a broad variety of preclinical investigation with great interest in translating its principles into clinical applications. Optical fluorescence imaging provides images of functional and structural changes with cellular and subcellular resolution in tissues at a low-cost. This technique takes advantage of the absorption of light photons at a specific wavelength by intrinsic or extrinsic fluorophores and emission of photons at characteristic wavelengths. The characteristics of the emitted wavelengths such as their energy and illuminance give substantial information of the imaged tissue. In the research presented here, we probe two Krebs cycle intrinsic fluorescence metabolic coenzymes, reduced nicotinamide adenine dinucleotide (NADH) and oxidized flavin adenine dinucleotide (FAD) to study metabolic status changes during a human disease. The objective of my research can be categorized into two themes; I) Designing an optical imaging instrument called an in vivo fluorescence imager to quantitatively investigate the metabolic changes in tissue and customizing it to be suitable for human/clinical studies. II) Using optical imaging techniques to quantitatively investigate the 3D anatomical structure changes in vessel structure of organs. in vivo fluorescence imager can image many intrinsic and extrinsic fluorophores. However, we used it to track mitochondria bioenergetics NADH and FAD in wounds of diabetic mice. We also define the redox ratio (NADH/FAD) as a biomarker to investigate the effect of 670 nm photo-biomodulation in those wounds. In another study, we have used 3D optical imaging system on the biopsy of diabetic wounds to confirm the results from the in vivo fluorescence imager. It showed that our in vivo fluorescence imager could successfully track the changes in the metabolic state of non-treated and treated diabetic wounds with 670 nm photobiomodulation. Additionally, I validated a 3D vessel segmentation method developed in our lab by employing Murray’s law. Furthermore, I used the 3D optical cryo-imaging system and the segmentation method to quantitatively study the 3D vessel structure changes in irradiated animal model. The result of this study showed that radiation can adversely change the vasculature in irradiated kidneys and negatively affect kidney perfusion. In summary, my major contribution has been in device implementation and applications of imaging and image processing in studies of animal model diseases of humans.
Keywords: 3D vessel segmentation; Diabetic wounds; irradiated kidneys; Optical imaging; redox ratio; Vessel Injuries